Spatial growth of Phnom Penh, Cambodia (1973–2015): Patterns, rates, and socio-ecological consequences. (September 2019) - Mialhe, François; Gunnell, Yanni; Navratil, Oldrich; Choi, Daniel; Sovann, Chansopheaktra; Lejot, Jérôme; Gaudou, Benoît; Se, Bunleng; Landon, Norbert
Highlights: Urban footprint of Phnom Penh increased from 3000 ha in 1973 to 25, 000 ha in 2015. Total loss of agricultural land over the period 1990–2015 amounts 21, 000 ha. Natural lakes and wetlands converted to urban spaces rose to 34% after 2006. Developments project benefits are unevenly distributed among the population. Evidence-based longitudinal analysis improves basis for policymaking options. Abstract: This work maps and interprets the evolution of the urban footprint of Phnom Penh from 1973 to 2015 and reviews its main socio-ecological impacts. The quantified patterns of urban growth and land-use change are based on the processing and analysis of Landsat satellite images (MSS, TM, and OLI sensors) and are enhanced by observation- and interview-based information obtained in the field. The growth of Phnom Penh is shown to have encroached initially on the fertile agricultural lands of the Mekong River floodplain, but since 2006 the city has been sprawling predominantly over natural lakes and wetlands that until then were functional components of the urban mosaic and underpinned the livelihoods of its population. Urban land areas increased from 3000 ha in 1973 to 4000 ha in 1990, subsequently soaring to 25, 000 ha in 2015, i.e. an average annual increase of 850–1000 ha. The discussion of these changes focuses on (i) changing livelihoods on the urban fringe; (ii) the numerous, and sometimes large, real-estate projects that have sprung up around the city centre on former wetland areas and are funded by strongly imbricated capital interests between the nation's elites and foreign investors; (iii) a comparison of the urban growth figures with other Asian cities; and (iv) current land policies in Cambodia. The results call for urgent policymaking to address the diseconomies that arise from the impending loss of ecosystem services; from the accentuation of flood hazards caused by the rapid, ongoing suppression of wetland habitats at the delta head of the eighth largest river in the world; and from the unequal distribution of the costs and benefits of urban growth among the metropolitan population.